A Constructive Beginning in Peasant Protest: “Red Army of Truth” in Buzuluk (July 1920) - D. A. Safonov (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The question of the content of the insurrectionary protest of the 1920s is considered. The relevance of the study is due to the tendency in historiography to develop any speech of this period in two directions: analysis of program and campaign documents and understanding of the process of suppressing protest. It is proposed to highlight the aspect of the implementation of program provisions for assessing the constructive beginning in the protest movement: how realizable were the programs of the rebels, and also how the rebels managed to implement their plans. Particular attention is paid to the performance of the “Red Army of Truth” in the summer of 1920, which the author defines as “communist” and pro-Soviet. The results of a comparative analysis of sources, which by their origin are related to the insurgent environment, and real actions of the insurgents are presented in the article. The novelty of the study is seen in the fact that the analysis of the actions of the insurgents is carried out without regard to the stereotypes existing in historiography and with the attraction of new facts from previously closed sources. A significant part of the plans and slogans of the “Army of Truth” were implemented in the controlled territory, which testifies to their realism. This allows us to question the well-established thesis that at that time the communist leaders in the center offered the only correct option for building a new Soviet state.